2013
DOI: 10.1037/a0031245
|View full text |Cite
|
Sign up to set email alerts
|

Early and prolonged exposure to reward delay: Effects on impulsive choice and alcohol self-administration in male rats.

Abstract: Naturally occurring impulsive choice has been found to positively predict alcohol consumption in rats. However, the extent to which experimental manipulation of impulsive choice may modify alcohol consumption remains unclear. In the present study, we sought to: (a) train low levels of impulsive choice in rats using early, prolonged exposure to reward delay, and (b) determine the effects of this manipulation on subsequent alcohol consumption. During a prolonged training regimen, three groups of male, adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
80
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 64 publications
13
80
5
Order By: Relevance
“…This suggests that timing precision, delay tolerance, and impulsive choice may all emerge from a common underlying factor. The current findings are also consistent with previous research demonstrating that exposure to reward and/or delay (Eisenberger and Adornetto 1986; Madden et al 2011; Stein et al 2013), and increased salience of delay (Zauberman et al 2009), can exert powerful effects on impulsive choice. However, these studies did not measure any concomitant effects on specific temporal processes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that timing precision, delay tolerance, and impulsive choice may all emerge from a common underlying factor. The current findings are also consistent with previous research demonstrating that exposure to reward and/or delay (Eisenberger and Adornetto 1986; Madden et al 2011; Stein et al 2013), and increased salience of delay (Zauberman et al 2009), can exert powerful effects on impulsive choice. However, these studies did not measure any concomitant effects on specific temporal processes.…”
Section: Discussionsupporting
confidence: 92%
“…Delay exposure could increase delay tolerance as the primary effect and improve the precision of timing as a secondary effect. Stein et al (2013) assessed the effect of exposure to either no delay, a fixed delay, or a progressively increasing delay on impulsive choice behavior. They found that exposure to either fixed or progressive delays increased LL choices compared to the no-delay condition, consistent with the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the former, rats completed a working-memory assessment that was similar to the training task; the latter was addressed by exposing our rats to 140 sessions of WMT. Second, if WMT could be used to experimentally reduce delay discounting in rats, then this would provide an opportunity to evaluate the causal relation between differences in delay discounting and subsequent propensity for drug-taking (Stein et al, 2013). …”
mentioning
confidence: 99%